2001
DOI: 10.1051/kmae:2001003
|View full text |Cite
|
Sign up to set email alerts
|

Taille À 3 Ans De La Truite Commune (Salmo Trutta L.) Dans Les Rivières Des Pyrénées Françaises : Relations Avec Les Caractéristiques Mésologiques Et Influence Des Aménagements Hydroélectriques.

Abstract: RÉSUMÉLa croissance de populations de truite commune (Salmo trutta L.) a été étudiée sur 84 cours d'eau répartis sur l'ensemble de la chaîne des Pyrénées. Pour cela, des échantillons d'écailles ont été récoltés dans 215 sites situés à des altitudes comprises entre 185 et 2000 m, pour des largeurs variant de 1,2 à 60 m. La croissance des individus a été déterminée par scalimétrie. La longueur totale moyenne atteinte par les individus à l'âge de 3 ans a été retenue comme variable biologique.La taille moyenne à 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…During the past century, the number of hydroelectric reservoirs drastically increased (Rosenberg et al, 1997), particularly in the French Pyrenees (Baran et al, 1995). Numerous studies have shown that such constructions induce disturbances to the Pyrenean river ecosystems (Baran et al, 1995; Lagarrigue et al, 2001; Lauters, 1992), suggesting that other natural systems could also be affected. Lacustrine sediments recording natural hazards and human activities are particularly relevant in assessing the consequences of future interventions on lacustrine systems.…”
Section: Introductionmentioning
confidence: 99%
“…During the past century, the number of hydroelectric reservoirs drastically increased (Rosenberg et al, 1997), particularly in the French Pyrenees (Baran et al, 1995). Numerous studies have shown that such constructions induce disturbances to the Pyrenean river ecosystems (Baran et al, 1995; Lagarrigue et al, 2001; Lauters, 1992), suggesting that other natural systems could also be affected. Lacustrine sediments recording natural hazards and human activities are particularly relevant in assessing the consequences of future interventions on lacustrine systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, en considérant 215 sites répartis sur 84 cours d'eau de la chaîne pyrénéenne, LAGARRIGUE et al (2001) ont montré que la taille à 3 ans des truites communes était 1) extrêmement variable selon les sites (de 128 à 314 mm), du fait de la très grande diversité écologique rencontrée dans les cours d'eau de cette région, 2) fortement structurée par le gradient altitudinal, ce dernier étant intégrateur d'un gradient thermique et physico-chimique, 3) pénalisée dans les secteurs soumis à des débits réservés.…”
Section: Introductionunclassified